The Influence of Brand Image, Product Innovation, and Social Media Marketing Activity on Repurchase Decision Through Customer Satisfaction as An Intervening Variable at Mixue In Bojonegoro - Dwi Fitrianti; Abdul Halik; Endah Budiarti (Journal of Social Research, 2025)
The development of the food & beverage (F&B) industry in Indonesia is currently growing very rapidly. Changes in people's lifestyles, especially in big cities, who like fast food and drinks, coupled with the passive use of digital platforms which have a transformative impact on digitalization provide opportunities for F&B businesses to promote their products to internet users. This research aims to find out empirical evidence regarding the influence of brand image, product innovation, social media marketing activity, on repurchase decisions and customer satisfaction. The population in this research are customers who have made purchases at Mixue Bojonegoro. The sampling technique is a purposive sampling technique which is randomly selected from customers who have made purchases at Mixue Bojonegoro, namely 100 respondents. Hypothesis testing was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Based on the results of the analysis of the 7 hypotheses analyzed, all were proven to be accepted, namely brand image, product innovation, and social media marketing activity had a significant effect on repurchase decisions and customer satisfaction. This research provides insight for companies in designing effective marketing strategies to increase customer loyalty through improving brand image, product innovation and marketing activities on social media.